Karakteristik Beras Analog Berbasis Tepung Jagung Terfermentasi dengan Suplementasi Tepung Daun Kelor (Moringa Oliefera) - Dini Nastiti Anjarasri; Teti Estiasih (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Analog rice is an alternative food developed from non-rice ingredients to diversify carbohydrate sources. This study examine the physical, chemical, and organoleptic characteristics of analog rice based on fermented corn flour with supplementation of Moringa oleifera leaf flour. The fermentation process on corn flour is intended to improve the functional properties of corn and enhance the quality of analog rice. The product formulation was carried out using a factorial Randomized Complete Block Design (RCBD) with two factors: the proportion of fermented corn flour to rice flour (60:40, 70:30, 80:20) and sodium alginate concentration (1%, 2%, 3%). Moringa leaf flour was supplemented at 0%, 10%, and 20%. The results indicated that the addition of fermented corn flour decreased brightness (L*) while increasing redness (a*) and yellowness (b*) of the product. Moringa supplementation increased protein and ash content but decreased carbohydrate and starch levels. Based on organoleptic tests, the best treatment was obtained from a combination of 70:30 fermented corn flour to rice flour, 3% sodium alginate, and 10% Moringa supplementation, producing analog rice with characteristics most similar to conventional rice. This study contributes to the development of nutritious and functional analog rice by utilizing local ingredients with great potential to enhance food security.